Efeito da intervenção eduterapêutica para prevenção de acidentes de trânsito com um grupo de crianças - Cartaxo, Carla Kalline Alves (2016)
Traffic accidents prevention must be taught since childhood, because children's behavior will be able to change the statistics of accidents in the long-term. This study aimed to evaluate the effectiveness of edutherapeutic intervention to prevent traffic accidents with children. It is characterized as a randomized controlled trial, conducted with 173 children from public school in northeast region of Brazil, divided into experimental group, EG (n = 90) and control group, CG (n = 83). Data collection took place in four stages in the second semester of 2014, with evaluation of variables: knowledge, attitudes and practices that reveal what children know, feel and how they behave in relation to this issue. Chi-square test was used for analysis of categorical variables. The t test was used in the EG to compare the moments before and after the intervention for the variables knowledge, attitudes and practices in the paired data, as well as the comparison between the moments of initial and final evaluations of CG and to compare EG and CG. The significance level used was 5%. The groups were similar regarding sociodemographic variables, form of transport of children, experience with traffic accidents and prevention. There was no difference in the level of knowledge, attitudes and practices among the groups at initial evaluation. In the final assessment, there was improvement in knowledge of EG (p = 0.027). It was also observed a tendency of improvement in attitudes (p = 0.06), not accompanied by significant increase in practices. Comparing EG before and after the intervention, there was a significant difference (p = 0.003) in relation to knowledge. Regarding CG, the initial and final assessment showed that children’s knowledge had greater number of correct answers at the initial evaluation, but no significant difference (p = 0.085), and there was a reduction in the level of appropriate attitudes and practices with significant difference, respectively (p = 0.033) (p = 0.003). The intervention increased the EG level of knowledge in relation to CG, however, attitudes and practices remained stable. In EG, the intervention increased the level of knowledge and kept the attitudes and practices at the same level. In the control group, the lack of intervention tended to have a negative impact on the level of appropriate attitudes and practices, and knowledge was affected, but not significantly. Thus, the intervention influenced significantly the practices and attitudes in comparison to knowledge.